HUBUNGAN ANTARA KOORDINASI MATA-KAKI DAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLE SEPAK BOLA PADA MAHASISWA FIK UNIMED : HUBUNGAN ANTARA KOORDINASI MATA-KAKI DAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLE SEPAK BOLA PADA MAHASISWA FIK UNIMED - Destya, Muhammad Reza (Universitas Negeri Medan, 2025)
This study aims to determine the relationship between eye-foot coordination and agility on the dribbling ability of students of the Faculty of Sport Science, State University of Medan. The population in this study were 148 students of class A, B, and C. Sampling was carried out using Purposive Random Sampling, namely 22 people as samples. Data analysis techniques used to test the hypothesis are normality test, linearity test, and correlation test. From the results of the first hypothesis correlation test, a significance value of 0.046 <0.05 was obtained, so there is a significant relationship between eye-foot coordination and the results of dribbling the ball. The results of the second hypothesis test, a significance value of 0.037 <0.05, so there is a significant relationship between agility and the results of dribbling the ball. Based on the multiple regression test, it is known that the significance of 0.037 <0.05, so H0 is rejected and Ha is accepted. This means that both independent variables (eye-foot coordination and agility) together have a significant relationship with the ability to dribble the ball.